19F-MRI for monitoring human NK cells in vivo. (3rd May 2016) - Bouchlaka, Myriam N.; Ludwig, Kai D.; Gordon, Jeremy W.; Kutz, Matthew P.; Bednarz, Bryan P.; Fain, Sean B.; Capitini, Christian M.
ABSTRACT: The availability of clinical-grade cytokines and artificial antigen-presenting cells has accelerated interest in using natural killer (NK) cells as adoptive cellular therapy (ACT) for cancer. One of the technological shortcomings of translating therapies from animal models to clinical application is the inability to effectively and non-invasively track these cells after infusion in patients. We have optimized the nonradioactive isotope fluorine-19 ( 19 F) as a means to label and track NK cells in preclinical models using magnetic resonance imaging (MRI). Human NK cells were expanded with interleukin (IL)-2 and labeled in vitro with increasing concentrations of 19 F. Doses as low as 2 mg/mL 19 F were detected by MRI. NK cell viability was only decreased at 8 mg/mL 19 F. No effects on NK cell cytotoxicity against K562 leukemia cells were observed with 2, 4 or 8 mg/mL 19 F. Higher doses of 19 F, 4 mg/mL and 8 mg/mL, led to an improved 19 F signal by MRI with 3 × 10 11 19 F atoms per NK cell. The 4 mg/mL 19 F labeling had no effect on NK cell function via secretion of granzyme B or interferon gamma (IFNγ), compared to NK cells exposed to vehicle alone. 19 F-labeled NK cells were detectable immediately by MRI after intratumoral injection in NSG mice and up to day 8. When 19 F-labeled NK cells were injected subcutaneously, we observed a loss of signal through time at the site of injection suggesting NK cell migration to distant organs. The 19 F perfluorocarbon is a safe and effective reagent for monitoring the persistence and trafficking of NK cell infusions in vivo, and may have potential for developing novel imaging techniques to monitor ACT for cancer.